[Buildings Construction at Husavik] - Streng, Evelyn Fiedler (1975)
Photograph of a building under construction in Husavik, Iceland. The grey, stone, rectangular building sits along a grassy hill covered in dark, rectangular windows and wooden scaffolding. The modern structure is grey with a flat roof and balconies line the sides of it. Several cars are sat parked in the grass alongside piles of rubble and wood outside the building.